Synthesis of scheme-cycle designs of absorption water-ammonia thermotransformers with extended degazation zone - Kosoy, Boris; Morozyuk, Larisa; Psarov, Sergii; Kukoliev, Artem (Eastern-European Journal of Enterprise Technologies, 2021)
The search for new and improvement of existing technical design of energy converter systems for specific consumers requires a reasonable choice of the most rational design for these objects. Thermotransformers that operate on the reverse and mixed thermodynamic cycles, in combination with power plants utilizing renewable and non-traditional primary energy (fuel), are considered to be of interest for small-scale power generation (trigeneration systems), which is consistent with the concept of distributed energy generation. Cold in trigeneration systems is provided by heat-using thermotransformers. This paper reports a method for synthesizing a scheme-cycle designs of absorption water-ammonia thermotransformers that utilize renewable heat sources with a low-temperature potential of 90–250 °С. A "cycle method" was applied to perform the thermodynamic analysis of the cycle of simple absorption thermotransformers with the expansion of the degazation zone with an increase in the temperature of the heating source; the technological schemes for the corresponding cycles have been substantiated. The influence of changing the degazation zone on the energy efficiency of the machine has been established. A scheme-cycle designs of the thermochemical compressor for a thermotransformer with a return supply of solutions to the generator and absorber at " excess temperatures" has been proposed, as a way to improve the cycle energy efficiency. A comparative analysis of the degree of thermodynamic perfection of the considered cycles has been performed using a specific example. The thermodynamic analysis demonstrated that the practical implementation of the scheme-cycle designs "with excess temperatures" could provide energy-saving conditions in small-scale trigeneration systems.